Meeting Individual Analyst Expectations - Kirk, Marcus P.; Reppenhagen, David A.; Tucker, Jennifer Wu (The Accounting Review, 2014)
ABSTRACT The expectations management literature has so far focused on firms meeting the analyst consensus forecast—the expectations of analysts as a group—at earnings announcements. In this study we argue that investors may use individual analyst forecasts as additional benchmarks in evaluating reported earnings because the consensus forecast underutilizes private information contained in individual analyst forecasts. We predict that measures reflecting such private information have incremental explanatory power over the consensus forecast for the market's reaction to earnings news. We find results consistent with this prediction by examining two measures: (1) the percentage of individual forecasts met and (2) meeting the key analyst forecast. We extend the literature by documenting the role of individual analyst forecasts in investors' evaluations of reported earnings. JEL Classifications: G10; G11; G17; G14; G24. Data Availability: Data are publicly available from the sources identified in the paper.